Keefektifan pembelajaran problem posing terhadap peningkatan prestasi dan minat belajar mahasiswa - Erlyka Setyaningsih (STKIP PGRI Banjarmasin, 2019)
The objective of this study was to describe and to compare the effectiveness of problem posing approach and conventional approach in terms of learning achievement and learning interest. The research design used quasi-experimental. The research population consist of all accounting student at Muhammadiyah Ponorogo University of the year 2017/2018 consisting of four classes. Student from class B and D were taken as sample. Class B as the control class was taught using convensional learning, while class D as the experiment class was taught using problem posing approach. The data collecting techniques were a test and non-test whereas the instrumens were used to collect the data consisted achievement test and interest questionnaire. The data were analyzed using MANOVA test, one sample t test, and two samples independent t test. The result of the study by using significance level 5%, showed that the problem posing approach was effective in terms of learning achievement and learning interest. Conventional aprroach was only effective in term of learning achievement. Problem posing approach was more excellent compared to conventional approach in terms of learning achievement and learning interest.